1989
DOI: 10.1002/food.19890330226
|View full text |Cite
|
Sign up to set email alerts
|

Light induced oxidation of nut oils (Short communication)

Abstract: The nuts are invariably sun-dried in Pakistan, Iran, Afghanistan and adjoining areas of China and USSR. Their oils are generally kept in the unrefined form, being exposed to light during subsequent handling or marketing and consequently undergo changes in colour, flavour and chemical changes. Light induced reactions have been found to damage the quality and stability of edible oils, fats and fat containing food products [l, 21. Oil characteristics of walnuts [3], and oxidation of almond and walnuts oils during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
4
5
0
6
Order By: Relevance
“…Our results are supported by previous published studies that report an increase in oil production subsequent to gamma irradiation in several plant species [15]. However, Dixit et al [13] determined that the nutritional features i.e.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are supported by previous published studies that report an increase in oil production subsequent to gamma irradiation in several plant species [15]. However, Dixit et al [13] determined that the nutritional features i.e.…”
Section: Discussionsupporting
confidence: 83%
“…A study of the effect of radiation involving gamma radiation (0.5, 1.0 and 1.5 kGy) on the lipids present in different plant nuts, revealed that the lipid extracted from the seeds have peroxide, anisidine and free fatty acid values higher than in non-irradiated samples [15].…”
Section: Discussionmentioning
confidence: 99%
“…Riboflavin may lose their activity and nutritive value decreases through light exposure. It may also lead to color changes and degradation of proteins (Sattar, 1989;Anonymous, 1993 …”
Section: Light Induced Changesmentioning
confidence: 99%
“…This effect is different from photo-oxidation which takes place in the presence of photosensitizer. The oxidation process is likely to be accelerated during retail storage as the kernels are often held at ambient temperature and relative humidity and are also exposed to light that catalyses oxidation (Sattar et al , 1989). Here the multifactorial effect on the oxidative stability of the nut is clearly evident.…”
Section: 33mentioning
confidence: 97%